Qualification of Fe0.95Co0.05Si2 as a reference material for high temperature measurement of the thermoelectric power factor. (15th February 2023) - Ziolkowski, Pawel; Edler, Frank; Stiewe, Christian; Haupt, Sebastian; Huang, Kai; Ryu, Byungki; Park, SuDong; Dasgupta, Titas; Sahu, Prashant; Taubmann, Rebekka; Müller, Eckhard
Graphical abstract: Abstract: Precise characterization of thermoelectric (TE) materials is mandatory for a meaningful validation of scientific results, focusing on traceable determination of the Seebeck coefficient ( S ), the electric ( σ ) and thermal ( κ ) conductivity. These properties form the thermoelectric figure of merit zT = ( S 2 σ / κ ) T, which is used for assessment of TE conversion efficiency with respect to the absolute temperature T . The level of metrological standardization is characterized to date by available reference samples for the Seebeck coefficient, publications on best practice measurement approaches, and accomplished international round robin (RR) campaigns on transport property measurements. We report on the qualification of β-Fe0.95 Co0.05 Si2 (FeSi2 ) as the first semiconducting high temperature reference material for the TE power factor ( PF  =  S 2 σ ), which is currently developed by the German Aerospace Center (DLR) and the Physikalisch-Technische Bundesanstalt (PTB). The relation between the size of FeSi2 compacts obtained by current-assisted short time sintering and the resulting functional homogeneity of the material is presented, which is studied by spatially resolved Seebeck coefficient measurements at room temperature. Data from temperature dependent characterization of the PF is provided to assess functional stability and homogeneity under integral measurement conditions. The outcome of certification measurements at PTB report on individual uncertainty contributions as the base for a later testimony of FeSi2 as a metrological reference for the PF . Integral measurements have been expanded to further comparative test results obtained by the Korea Electrotechnology Research Institute (KERI), the Indian Institute of Technology Bombay (IITB), and the Netzsch Gerätebau GmbH. The findings give evidence of an excellent homogeneity, reproducibility and stability with low standard deviations for S and σ far below typical measurement uncertainties, which effectively demonstrates the suitability of FeSi2 as a future reference material for TE metrology at elevated temperatures up to 1000 K.